(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
As rotating packed beds (RPBs) gain prominence in intensified mass transfer operations, efficient packing design is critical for optimizing performance. Traditional packing structures often face limitations in terms of pressure drop, wetting efficiency, and fluid distribution. 3D-printed packings offer new possibilities by allowing complex geometries tailored to specific fluid dynamics. This study presents a detailed comparison of the performance of standard wire mesh packings and an anisotropic 3D-printed packing, focusing on pressure drop variations under varying operational conditions. Compared to the standard packing, the hydrodynamic performance of the 3D printed packing showed a lower pressure drop of about 0.7kPa at the combination of maximum operating conditions investigated of 300Nm3/h, 1000 rpm, and 0.72m3/h in the gas flow, rotation speed, and liquid glow rate respectively. The wet pressure drop per unit packing length of the 3D packing compared favourably with the standard wire mesh packing. The 3D-printed RPB packings proved to be a promising way that has the potential to enhance the separation performance of RPBs.